2020
DOI: 10.1186/s13020-020-00334-w
|View full text |Cite
|
Sign up to set email alerts
|

The mediatory role of Majie cataplasm on inflammation of allergic asthma through transcription factors related to Th1 and Th2

Abstract: Background Asthma, a common respiratory disease, is harmful biological effect to our health. As a traditional Chinese medicine for asthma, Majie cataplasm could alleviate the symptoms of asthma and its compositions have immunomodulatory effects. Previous experiments showed that Majie cataplasm was an effective approach to mitigate asthma airway remodeling and had the potential to regulate Th2 cytokines of IL-5 and IL-13. Therefore, our further research focuses on the explanation about the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
(49 reference statements)
1
8
0
Order By: Relevance
“…Adaptive lymphocytes, therefore, has clearly added a selective advantage compared to that of ILCs in conferring protective immunity under natural conditions. In our previous study, Majie cataplasm could reduce the increasing number of Th1 and Th2 in the asthma model group, which meant that the adaptive cells supported the leading role in asthma inflammation [ 20 ]. And in order to confirm this, we detected other adaptive cells, Treg and B10s.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adaptive lymphocytes, therefore, has clearly added a selective advantage compared to that of ILCs in conferring protective immunity under natural conditions. In our previous study, Majie cataplasm could reduce the increasing number of Th1 and Th2 in the asthma model group, which meant that the adaptive cells supported the leading role in asthma inflammation [ 20 ]. And in order to confirm this, we detected other adaptive cells, Treg and B10s.…”
Section: Discussionmentioning
confidence: 99%
“…For a mouse, the area is 0.2 cm 2 . The production flow chart of Majie cataplasm was referred to our previous study [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was observed in a murine asthma model that treatment with a novel H 4 R antagonist (N-(2-Aminoethyl)-5-chloro-1H-indole-2-carboxamide) decreased the activation of ERK1/2, Akt, SAPK/JNK and NF-κB signaling pathways, in addition to reduced Th2 cytokines production in BAL and eosinophilic infiltration in lung tissue [14]. Activation of the STAT3 signaling pathway proved to be important for Th2 cells differentiation, cytokines production, allergic inflammatory response increasing and airway remodeling [53,54]. Studies showed that inhibition of the STAT3 signaling pathway in mast cells impaired FcεRI-mediated signaling and reduced degranulation in humans [55].…”
Section: Discussionmentioning
confidence: 99%